Infants As Corporate Shareholders: The Position In Malaysia - Kamaliah, Salleh; Noor ‘Ashikin, Hamid; Noraida, Harun; Asiah, Bidin; Zuhairah Ariff, Abd Ghadas (2017)
Family business owners sometimes incline to have their family members to benefit from the business by making them as shareholders in the incorporated family business. Infants or minor children are not excluded from being given similar opportunity to have such stake in the company. The Act 777 (Companies Act 2016) does not prescribe the age requirement for a person to effectively become a shareholder in a company. Thus, it is important for this paper to investigate the issues regarding the legality of infants to own shares, and the implications arising pursuant to their status as shareholders. The study is based on qualitative approach which employs library research method for data collection. The study analyses various texts such as statutes, books, journals and reports. The study reveals that although there is no statutory restrictions in the Act 777 alone for an under-aged person to hold shares, infants are exposed to various legal consequences as shareholders, hence entails deep consideration by the family especially parents or guardians before they ultimately decide to make their infants as shareholders in their company.